2017
DOI: 10.21815/jde.017.036
|View full text |Cite
|
Sign up to set email alerts
|

Dental Therapists as New Oral Health Practitioners: Increasing Access for Underserved Populations

Abstract: The development of dental therapy in the U.S. grew from a desire to find a workforce solution for increasing access to oral health care. Worldwide, the research that supports the value of dental therapy is considerable. Introduction of educational programs in the U.S. drew on the experiences of programs in New Zealand, Australia, Canada, and the United Kingdom, with Alaska tribal communities introducing dental health aide therapists in 2003 and Minnesota authorizing dental therapy in 2009. Currently, two addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 13 publications
(20 reference statements)
0
36
0
Order By: Relevance
“…Combining dental therapy and dental hygiene curricula has been an international trend 14,16,33 since the 1990s and is evident in Australia, 34 New Zealand, 35 United Kingdom, 36 and the Netherlands. 37 According to Nash, the graduates of such programs are increasingly referred to as "oral health therapists" (OHTs).…”
Section: Educational Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining dental therapy and dental hygiene curricula has been an international trend 14,16,33 since the 1990s and is evident in Australia, 34 New Zealand, 35 United Kingdom, 36 and the Netherlands. 37 According to Nash, the graduates of such programs are increasingly referred to as "oral health therapists" (OHTs).…”
Section: Educational Modelsmentioning
confidence: 99%
“…More than 50 countries have integrated providers with dental therapy abilities, 14 and their positive impact on access to safe, cost-efective oral services is well documented. [14][15][16][17][18][19] According to Phillips and Shafer, "Rather than representing a diferent standard of care, dental therapists simply represent a diferent provider." 18 Recent studies have found that many oral health needs of populations that are underserved could be met by providers with a combination of dental hygiene and dental therapy abilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If Medicaid-enrolled adults below 250% of the Federal Poverty Level were provided with basic dental benefits, it would certainly increase utilization rates, at least initially. 25 Nevertheless, such legislation is periodically being introduced in other states, suggesting that this could change. Thus, greater demand from low-income adults would likely be well within the capacity of the current care system.…”
Section: Current Supply Of Dentists and Population Demandmentioning
confidence: 99%
“…Few other states have legalized the use of dental therapists, and it would take many years before a large enough number of dental therapists is available to make a significant difference. 25 Nevertheless, such legislation is periodically being introduced in other states, suggesting that this could change. On the other hand, dental hygienists in many states are providing screening and primary and second-ary preventive services to children in school-based delivery systems and in private practices.…”
Section: Current Supply Of Dentists and Population Demandmentioning
confidence: 99%